Virus-specific CD8+ T lymphocytes within the normal human liver. - Ward, S; Jonsson, JR; Sierro, S; Clouston, A; Lucas, M; Vargas, A; Powell, E; Klenerman, P (2004)
The frequency and phenotype of human antiviral memory CD8(+) T cells in blood are well studied, yet little is known about their distribution within tissues. Analysis of antiviral CD8(+) T cell populations derived from a unique set of normal liver and blood samples identified a consistent population of virus-specific cells within the liver. In comparison to the circulating T cells, the liver-derived T cells were present at frequencies which were variably enriched compared to that in the blood, and showed significant differences with regard to the expression of CD45RA, CD45RO, CD95, CCR7, CD27 and CD28. The differences in these cell surface markers are consistent with a mature 'effector memory' phenotype of antigen-specific CD8(+) T cells within the liver. An enrichment of an activated subset of NKT cells (V alpha 24/V beta 11) was also observed, a finding which may be relevant to the regulation of the antiviral populations.